ALBERT ADDS UP! - May, Eleanor; Melmon, Deborah (New York, NY : AV2 by Weigl, 2019)
AV2 Fiction Readalong by Weigl brings you timeless tales of mystery, suspense, adventure, and the lessons learned while growing up. These celebrated childrens stories are sure to entertain and educate while captivating even the most reluctant readers. Log on to www.av2books.com, and enter the unique book code found on page 2 of this book to unlock an extra dimension to these beloved tales. Real actors will bring the story to life as you read along in your own book.
First published in the United States of America in 2014 by Kane Press, Inc.
3 - 6 years.
Keywords: Readers -- Juvenile fiction; Books and reading -- Juvenile fiction; Addition -- Juvenile fiction; Mathematics -- Juvenile fiction; Barter -- Juvenile fiction; Picture books